AUTONOMIC COMPUTING FOR PROCESSING THE COMPLEX WEB SERVICE (International Journal of Scientific Research and Management (IJSRM), 2017)
Quality of Service (QoS) analysis for Web service compositions is an important and challenging issue in distributed computing. In existing work, there is a systematic approach is followed to calculate QoS for composite services with complex structures. This method is not effective to find the path probability information’s as well as there is some restrictio ns to find the full path. In fact this existing method can’t be the best solution for the optimum performance. Hence this project proposes QoS Ontology with ETQoS: Enhanced Transactional and QoS-Aware Selection Algorithm for Automatic Web Service Composition. The design which builds a general QoS ontology to support web services nonfunctional features. This process addresses the issue of selecting and composing Web services not only according to their functional requirements but also to their transactional properties and QoS characteristics. This method can also satisfy the user’s preferences over QoS criteria. Experimental results show that the proposed ETQoS calculation approach significantly improves the efficiency in probabilistic QoS estimation